(untitled) (Doctor Virtualis, 2023)
We are in an era of rapid evolution of scholarly communication. The inaccessibility of quality texts, data, and processes is being replaced by a choral demand for transparency, equity, and democraticity. The idea of a competitive and exclusive science is replaced by that of a collaborative science in which the sharing of results is the founding value and strength for faster development. The role of commercial publishers who must reinvent themselves in this new context changes and is challenged; the balance of power between editors, reviewers and authors changes. The tools for responding to this choral demand for transparency are all at our disposal, but still from the scientific communities there is some difficulty in taking on board the new ways of practicing, validating and disseminating research. There is still some distrust and perhaps dismay in front of possible audiences and a research life cycle that is potentially never-ending. On the shoulders of giants, Newton quoted. And this is especially true if the economic and legal barriers that have hitherto been an obstacle, or at least a slowdown to the development of scientific research are removed. "Doctor Virtualis" is a humanistic journal that embraced in rather distant times the philosophy of openness promoted by the university that has proved successful today. Its story is the story of the journal platform that hosts it to which the journal has joined since its first year.